SUMBER DAN FUNGSI PENDAPATAN ASLI DAERAH - Mia Siratni (Ensiklopedia Sosial Review, 2022)
The implementation of regional government functions will be carried out optimally if the administration of government affairs is followed by providing adequate sources of revenue to the regions, with reference to the Law on Financial Balance between the Central Government and Regional Governments, where the amount is adjusted and harmonized with the division of authority between the government and the regions. All financial sources attached to every government affair that are handed over to the regions become a source of regional finance. Local government finance is a very decisive factor in the administration of local government. Regional financial capacity is determined by the existence of regional income sources and their lucrative level. The lucrative level of local revenue sources is determined by the extent to which the tax base is responsive to inflation, population growth and economic growth. In general, developed countries that implement decentralization policies tend to give greater authority to regions to manage lucrative sources of income. On the other hand, in developing countries, lucrative financial resources are controlled by the center. Local governments only manage financial resources that have less potential.